Long-term treatment with romiplostim in patients with chronic immune thrombocytopenia: safety and efficacy - D. J. Kuter; J. B. Bussel; A. Newland; R. I. Baker; R. M. Lyons; J. Wasser; J.-F. Viallard; G. Macik; M. Rummel; K. Nie; S. Jun (Онкогематология)
Romiplostim was effective, safe, and well-tolerated over 6–12 months of continuous treatment in Phase 3 trials in patients with immune thrombocytopenia (ITP). This report describes up to 5 years of weekly treatment with romiplostim in 292 adult ITP patients in a long-term, single-arm, open-label study. Outcome measures included adverse events (including bleeding, thrombosis, malignancy, and reticulin / fibrosis), platelet response (platelet count >50 × 109 per litre), and the proportion of patients requiring rescue treatments. Treatment – related serious adverse events were infrequent and did not increase with longer treatment. No new classes of adverse events emerged. Thrombotic events occurred in 6.5 % of patients and were not associated with platelet count. Median platelet counts of 50–200 × 109 per litre were maintainedwith stable doses of romiplostim (mean 5–8 μg / kg; generally self-administered at home) throughout the study. A platelet response was achieved at least once by 95 % of patients, with a platelet response maintained by all patients on a median 92 % of study visits. There was a low rate of bleeding and infrequent need for rescue treatments. In conclusion, this study demonstrated that romiplostim was safe and welltolerated over 614 patient-years of exposure in ITP patients, and that efficacy was maintained with stable dosing for up to 5 years of continuous treatment.